Saussurea lappa Ethanolic Extract Attenuates Triamcinolone Acetonide-Induced Pulmonary and Splenic Tissue Damage in Rats via Modulation of Oxidative Stress, Inflammation, and Apoptosis - Ghada I. Abd El-Rahman; Amany Behairy; Nora M. Elseddawy; Gaber El-Saber Batiha; Wael N. Hozzein; Dina M. Khodeer; Yasmina M. Abd-Elhakim (MDPI AG, 2020)
Background: In this era, worldwide interest has been directed towards using natural antioxidants to guard against drug side effects. Saussurea lappa is a famous medicinal plant with many biologically active compounds. Triamcinolone acetonide (TA) is an extensively used glucocorticoid. Hence, this study explored, for the first time, the possible beneficial effects of S. lappa ethanolic extract on TA-induced oxidative damage in the lung and spleen of rats. Methods: Five experimental groups were used: control group, S. lappa-treated group (600 mg/kg/day, orally), TA-treated group (40 mg/kg/twice/week I/P), S. lappa + TA co-treated group, and S. lappa/TA prophylactic group. Results: TA exposure significantly induced leukocytosis and neutrophilia. In addition, TA significantly reduced the levels of C-reactive protein, interleukin-12, tumor necrosis factor α, and immunoglobulins. Lung Caspase-3 overexpression and splenic CD8+ downregulation were also noted in the TA group. TA treatment significantly increased malondialdehyde concentration but reduced superoxide dismutase and glutathione peroxidase activities. S. lappa counteracted the TA oxidative and apoptotic effects. The best results were recorded in the prophylactic group. Conclusions: S. lappa has a remarkable protective effect via its anti-inflammatory, anti-apoptotic, and antioxidant capacity. Thus, it could be a candidate as a natural antioxidant to face glucocorticoid's harmful side effects.